Experience in the diagnosis and treatment of pneumonia caused by infection with Tropheryma whipplei: A case series - Zhixiong Fang; Qiong Liu; Wei Tang; Hongyin Yu; Min Zou; Haiming Zhang; Haiyan Xue; Sha Lin; Yi Pei; Jingwen Ai; Jun Chen (Heliyon, 2023)
Tropheryma whipplei (TW) is the root cause of Whipple’s disease (WD), a rare infectious illness leading to multi-organ impairment. A prominent feature of WD is acute pneumonia, which can be exceedingly challenging to diagnose clinically due to the pathogen’s surreptitious nature. However and significantly, with the advent of metagenomic next-generation sequencing (mNGS) of bronchoalveolar lavage fluid (BALF), it offers clinicians a potent tool at their disposal to detect TW infections. The present study conducted a retrospective analysis of clinical data gleaned from five patients in Hunan Province in China. Findings in this study demonstrated the potential of BALF-mNGS in diagnosing pneumonia caused by TW infection.